2000
DOI: 10.1007/s001340051170
|View full text |Cite
|
Sign up to set email alerts
|

Effect of positive end-expiratory pressure on splanchnic perfusion in acute lung injury

Abstract: PEEP by itself does not have a consistent effect on splanchnic blood flow and metabolism when cardiac index is stable and patients are ventilated within the linear part of the pv curve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 24 publications
5
28
0
1
Order By: Relevance
“…On further analyses, the investigators were able to identify two independent risk factors predictive of clinically important bleeding: Prolonged mechanical ventilation and coagulopathy, it is unclear why artificial ventilation leads to an increase in upper GI bleeding. In a prospective study, Kiefer et al [15] found no change in gastric mucosal-arterial pCO 2 difference in patients with acute lung injury and increasing PEEP levels, as long as cardiac output was stable. Sympathetic stimuli decrease mucosal blood flow [16].…”
Section: Commentmentioning
confidence: 97%
“…On further analyses, the investigators were able to identify two independent risk factors predictive of clinically important bleeding: Prolonged mechanical ventilation and coagulopathy, it is unclear why artificial ventilation leads to an increase in upper GI bleeding. In a prospective study, Kiefer et al [15] found no change in gastric mucosal-arterial pCO 2 difference in patients with acute lung injury and increasing PEEP levels, as long as cardiac output was stable. Sympathetic stimuli decrease mucosal blood flow [16].…”
Section: Commentmentioning
confidence: 97%
“…In addition, Holland et al [22] showed that a PEEP of 10 cm H 2 O did not affect the indocyanine green plasma disappearing rate (ICG PDR ), a dynamic liver function test, or gastric mucosal perfusion after cardiac surgery. Kiefer et al [23] studied the effect of PEEP on splanchnic perfusion in patients with acute lung injury. They showed that PEEP itself did not have a consistent effect on hepatic-splanchnic blood flow or liver metabolism if CI remained stable.…”
Section: Discussionmentioning
confidence: 99%
“…Knowing when to apply full lung-protective modes may be particularly important in patients undergoing OLT as the use of positive end-expiratory pressure (PEEP) may decrease hepatic blood flow, possibly by decreasing the cardiac output. 33,34 However, 2 clinical studies evaluating the effects of PEEP on liver graft function did not observe any deleterious effects on systemic hemodynamic or liver graft function at PEEP levels 10 or even 15 cm H 2 O. 35,36 Moreover, because increased ELWI may be associated with pleural effusions, early detection and drainage may be useful for facilitating MV.…”
Section: Anesthesia and Analgesiamentioning
confidence: 98%